TRUST IN CHATGPT: AN EMPIRICAL ANALYSIS OF THE INFLUENCING FACTORS - Stegner, Maria (My University, 2024)
ChatGPT has taken the world by storm, growing faster than any other platform in history. With the rapid emergence and adoption of ChatGPT the issue of trust into the technology and its answers becomes an important issue. With a series of semi-structured interviews this paper examines the factors affecting trust into ChatGPT itself and the output the algorithm provides. The study suggests that peer’s positive opinions on the algorithm increase trust on ChatGPT and occupational background has an impact on it. Perceived data privacy risks and negative perceptions of ChatGPT’s future impact were found to decrease trust in ChatGPT. Trust in ChatGPT’s output was shown to positively correlate with increased experience using ChatGPT.
Keywords: ChatGPT, trust